Strategi Pemasaran Sekolah Dalam Peningkatan Minat Peserta Didik Berdasarkan Delta Model - Ririn Tius Eka Margareta; Bambang Ismanto; Bambang Suteng Sulasmono (Universitas Kristen Satya Wacana, 2018)
The purpose of this study is to develop a school marketing strategy in increasing customer interest. This research is limited to the stage of product manufacturing. Data were collected using documentation study, observation, and in-depth interviews. Data is validated by source and techniques triangulation. Data analysis techniques using Miles and Huberman Model (interactive model): data reduction, presentation data, and conclusion/verification. The result of this research: 1) the implemented strategy is to use a promotional strategy by spreading brochures and/or presentations to predetermined schools and churches, word of mouth organizing month language events every year, and activities/program held/followed by school, 2) obstacles and lack of marketing strategy implemented by this school in increasing the interest of learners that time management is not right, committee less active, foundation not yet involved, dissemination of brochure less effective, marketing is less extensive, does not yet have a document of school marketing strategy, and has not been able to ensure and communicate that the services offered are relevant to the needs of the community, and 3) The resulting product is a school marketing strategy based on the Delta Model in the interest of learners: a) Best Product Strategy: conducting holistic education through various school activities/programs that are unique and relevant to customer needs, and apply multi payment system to simplify customer conduct financial transactions; b) Total Customer Solutions Strategy: maximize resources owned by the company and facilitate the human resources who participate in the competitions/activities to meet their needs, and give appreciation of the effort/achievement of human resources; and c) System Lock-In Strategy: enforcing contract system with certain experts/clients within a certain period of time to lock customer, implement career path system for teachers and school staff, and have special cooperation and instructions which applies to alumni, high school favorites, certain universities, and other educational institutions.